Ecological Adaptation and Local Wisdom in the Petik Laut Tradition in Lapa Laok Village, Sumenep - Ghufron, Muhammad; Bahri, Moh. Syaiful; Ahmad Rizal, Derry (Universitas Islam Negeri Raden Intan Lampung, 2026)
The Petik Laut tradition represents a form of local wisdom among coastal communities that reflects the close relationship between humans, the environment, and belief systems. Amid increasing ecological challenges, this cultural practice becomes important to examine as a form of community adaptation to environmental changes. This study aims to analyze the Petik Laut tradition in Lapa Laok Village, Sumenep, as a manifestation of ecological adaptation among coastal communities through a cultural ecology approach. This research employs a qualitative method, with data collected through observation, in-depth interviews, and documentation involving community leaders and participants of the tradition. The data were analyzed through processes of reduction, display, and verification to identify patterns of interaction between culture and the environment. The results indicate that the Petik Laut tradition serves not only as a ritual of gratitude but also as a mechanism for ecological adaptation, reflected in practices such as the temporary suspension of fishing activities, the preservation of water resources through the protection of wells, and the prohibition against cutting down large trees in specific areas. Furthermore, the integration of religious, social, and ecological values at every stage of the ritual strengthens the community’s collective awareness of maintaining environmental balance. This study contributes to the field of cultural ecology by demonstrating that local traditions are not merely cultural heritage but also serve as sustainable strategies for addressing socio-ecological challenges at both local and global levels.